(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was conducted to identify the constraints faced by the members of SHGs and JLGs in dairying in Barpeta and Kamrup districts of Assam. A total of 100 respondents selected and information on their dairy characteristics and problems faced by them in dairy farming were elicited through a structured, reliable and valid interview schedule. The result shows about that high cost of feeds and fodder (83%), lack of quality breed (60%); inadequate veterinary facilities (56%), marketing (47%) etc were the major challenges of dairying to mitigate.